2020
DOI: 10.2478/aucft-2020-0017
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Peroxidase Activity of Turnip (Brassica rapa) Using Response Surface Methodology

Abstract: The present study is focused on the determination of optimized activity conditions of peroxidase (POD) of turnip (Brassica rapa). The enzyme is extracted from turnip with 0.5M Na2HPO4 (pH7.0). Peroxidase activity is evaluated by monitoring the oxidation of guaiacol to tetraguaiacol in the presence of hydrogen peroxide (H2O2). Before the optimization of peroxidase activity from a turnip by response surface methodology (RSM), a preliminary step is conducted for each studied parameter (pH, temperature, and NaCl c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The pH of the medium impacts the microbe's net charge, affecting its enzymatic production physiology (Makapela et al 2016). Turnip POX at pH 8 and 30 °C gave maximum activity (4027 U/mg) (Dahdouh et al 2020). Falade et al (2019) reported 5.9 pH at 30 °C in Ensifer adhaerens POX.…”
Section: Effects Of Ph Value Temperature and Incubation Days On Pox A...mentioning
confidence: 99%
“…The pH of the medium impacts the microbe's net charge, affecting its enzymatic production physiology (Makapela et al 2016). Turnip POX at pH 8 and 30 °C gave maximum activity (4027 U/mg) (Dahdouh et al 2020). Falade et al (2019) reported 5.9 pH at 30 °C in Ensifer adhaerens POX.…”
Section: Effects Of Ph Value Temperature and Incubation Days On Pox A...mentioning
confidence: 99%
“…Peroxidases (PODs) (E.C 1.1.11.7), which are in the oxidoreductase enzyme class, are responsible for electron exchange from a natural substrate (hydrogen peroxide, H 2 O 2 ) to another synthetic compound (guaiacol) 1 . They can contribute to H 2 O 2 reduction while oxidizing a second substrate.…”
Section: Introductionmentioning
confidence: 99%
“…H 2 O 2 ) to another synthetic compound (guaiacol). 1 They can contribute to H 2 O 2 reduction while oxidizing a second substrate. These enzymes are among the key critical antioxidant biocatalysts involved in detoxifying reactive oxygen species (ROS) and preventing oxidative stress.…”
mentioning
confidence: 99%